483 Research 101: Building the Research Skills of Practicing Clinicians. (April 2022) - Dawson, Amy P.; Callahan, Kathryn E.; Perry, Anna; Olivier, Claudia; Munn, Lindsay T.
Abstract : OBJECTIVES/GOALS: The goal was to develop foundational research knowledge and skills for clinicians interested in conducting clinical research. Emphasis was on the development of a research question and the iterative process necessary to transform a research question into a well-designed study and well-articulated research proposal for pilot grant funding. METHODS/STUDY POPULATION: The course took place over 10 sessions, May - September 2021. The application process required participants to provide an initial self-assessment of research skills and a proposed research question. 25 clinicians applied to the program, 11 were accepted, and 9 enrolled. All clinicians in the initial cohort were clinical faculty physicians. Because of the geographical distance of participants as well as the ongoing pandemic, the course used a blended learning approach with both synchronous and asynchronous learning. Participants viewed online lectures on core content coupled with live virtual sessions with opportunities for discussion and application of the content. Relevant CTSI and institutional resources were highlighted in each session. RESULTS/ANTICIPATED RESULTS: Of the 9 clinician participants who enrolled in Research 101, the average attendance per session was 67% or 6 people. 89% or 8 participants attended five or more sessions. 5 participants submitted a letter of intent for the annual CTSI Pilot grant program, and of the five, two were invited to submit a grant application. Formal evaluation of the program is currently ongoing and will close on November 30th, at which time full results will be available. Research competencies will be assessed through a pre-post comparison, each self-rated by course participants. Additionally, participants were asked to provide input on the most and least valuable components of the course, as well as any open-ended feedback. Research 101 leadership will use these results to improve the course for future participants. DISCUSSION/SIGNIFICANCE: A learning health system (LHS) is recognized as an essential means by which research evidence is translated into practice. Important to realizing the LHS vision is the engagement of clinicians into the generation and translation of research into practice. Research 101 is an important way to bolster clinician engagement in translational research.